Evolution and Performance of Exchange Rate Regimes - Brooks, Robin (Occasional Papers; Occasional Paper ;, 2004)
The issue of the appropriate exchange rate regime for individual countries has been perennially lively, and the role played by international capital flows and domestic financial systems in determining the performance of these regimes has gained prominence in the policy debate. Using recent advances in the classification of exchange rate regimes, the key message in this paper is that, as economies and their institutions mature, the value of exchange rate flexibility increases. This study assesses the historical durability and performance of alternative exchange rate regimes, with special focus on developing and emerging market countries. It describes trends in the distribution of regimes and examines the transitions between regimes. It also reviews the performance of exchange rate regimes in terms of inflation and business cycles.